Assessment of carbon sequestration as affected by different management practices using the RothC model - Prudil, Jakub; Pospíšilová, Lubica; Dryšlová, Tamara; Barančíková, Gabriela; Smutný, Vladimír; Sedlák, Luboš; Ryant, Pavel; Hlavinka, Petr; Trnka, Miroslav; Halas, Ján; Koco, Štefan; Takáč, Jozef; et al. (Česká akademie zemědělských věd, 2023)
Long-term field experiments provide a valuable dataset for predicting changes in soil organic carbon (SOC) stocks in different agricultural systems. The RothC-26.3 model was used to simulate changes in SOC in the monoculture of spring barley (Hordeum vulgare L.) and the Norfolk crop rotation during 1972-2100. The potential of the Gleyic Fluvisol Clayic to sequester organic carbon was investigated. The studied soil was heavily textured, with medium organic carbon content. Four management scenarios in the monoculture and six management scenarios in the Norfolk crop rotation were evaluated. Three different global climate models (MPI, MRI, CMSS) representing the uncertainty of future climate conditions were used. Results showed that carbon stocks were mainly influenced by plant residue inputs and exogenous organic materials application. The projection showed trends of carbon stocks decreasing in the case of monoculture management. Results also documented that management scenario D with straw incorporation and intercrops represented sustainability and carbon stock increase during all modelled climate scenarios. The SOC stock at the end of the century was approximately 66 t/ha. This represents a moderate sequestration of SOC of approximately 0.09 t/ha/year.
Keywords: organic carbon accumulation; crop management and climatic conditions; modelling